Medical Imaging 2020: Digital Pathology 2020
DOI: 10.1117/12.2549061
|View full text |Cite
|
Sign up to set email alerts
|

Using a 22-layer U-Net to perform segmentation of squamous cell carcinoma on digitized head and neck histological images

Abstract: Squamous cell carcinoma (SCC) comprises over 90 percent of tumors in the head and neck. The diagnosis process involves performing surgical resection of tissue and creating histological slides from the removed tissue. Pathologists detect SCC in histology slides, and may fail to correctly identify tumor regions within the slides. In this study, a dataset of patches extracted from 200 digitized histological images from 84 head and neck SCC patients was used to train, validate and test the segmentation performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“… 24 Mavuduru et al evaluated the ability of a CNN using U-Net tested on 200 tissue samples from 84 HNSCC patients from a single center. Their study showed an AUC of the testing group of 0.89, with a threshold of 0.2845 and average time of segmentation from WSI to be 72 s. 25 In the study of Rodner et al, a CNN was used to diagnose HNSCC distinguishing between cancer, normal epithelium, background stroma, and other tissue types on 114 images from 12 patients. Average and overall recognition rates for the 4 classes were 88.9% and 86.7%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“… 24 Mavuduru et al evaluated the ability of a CNN using U-Net tested on 200 tissue samples from 84 HNSCC patients from a single center. Their study showed an AUC of the testing group of 0.89, with a threshold of 0.2845 and average time of segmentation from WSI to be 72 s. 25 In the study of Rodner et al, a CNN was used to diagnose HNSCC distinguishing between cancer, normal epithelium, background stroma, and other tissue types on 114 images from 12 patients. Average and overall recognition rates for the 4 classes were 88.9% and 86.7%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Popular CNNs like UNet and Inceptionv4 have shown significant promise in identifying and localising regions of abnormality on digital slides for oral squamous cell carcinoma (34; 35). With the aid of DL methods, Nanditha et al (36) developed an automated system to examine oral lesions.…”
Section: Related Workmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC), the seventh most common cancer globally, accounts for 890 000 new cases and 450 000 deaths annually (Barsouk et al 2023). It is often curable if diagnosed at an early stage with a 5 year overall survival rate over 90% and below 50% for late stage diagnosis (Mavuduru et al 2020, FH et al 2021.…”
Section: Introductionmentioning
confidence: 99%